2015
DOI: 10.1089/omi.2015.0057
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Medicine and Multi-Omics Research for Future Nutrition Targets: Metabolomics and Transcriptomics of the Common Degenerative Mitral Valve Disease in Dogs

Abstract: Canine degenerative mitral valve disease (DMVD) is the most common form of heart disease in dogs. The objective of this study was to identify cellular and metabolic pathways that play a role in DMVD by performing metabolomics and transcriptomics analyses on serum and tissue (mitral valve and left ventricle) samples previously collected from dogs with DMVD or healthy hearts. Gas or liquid chromatography followed by mass spectrophotometry were used to identify metabolites in serum. Transcriptomics analysis of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 43 publications
3
62
1
Order By: Relevance
“…The current study showed decreased expression of cfa-miR-302d in the serum of dogs with MMVD. This, along with previous observations in dogs with MMVD of increased gene and protein expression of fibronectin and TβRI/TβRII, respectively in the MV [ 34 , 35 ] and increased thrombospondin 1 in LV and MV and thrombospondin 4 in the LV [ 31 ], suggest a potential role of cfa-miR-302d / TGF-β regulatory network in the pathology of MMVD in dogs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The current study showed decreased expression of cfa-miR-302d in the serum of dogs with MMVD. This, along with previous observations in dogs with MMVD of increased gene and protein expression of fibronectin and TβRI/TβRII, respectively in the MV [ 34 , 35 ] and increased thrombospondin 1 in LV and MV and thrombospondin 4 in the LV [ 31 ], suggest a potential role of cfa-miR-302d / TGF-β regulatory network in the pathology of MMVD in dogs.…”
Section: Resultssupporting
confidence: 86%
“…In a previous canine gene expression study (National Center for Biotechnology Information’s Gene Expression Omnibus (GEO) Accession No. GSE64544) [ 31 ], we found that Trx1 was upregulated 2.6-fold ( p = 0.002) in the LV, while angiotensinogen, the precursor of Ang II , was downregulated by more than 8-fold ( p ≤ 0.001) in the mitral valve (MV) of dogs with MMVD. This suggests that the Trx1-let-7 / miR-98-Ang II regulatory circuitry may also exist in canine MMVD and CHF.…”
Section: Resultsmentioning
confidence: 99%
“…In the postgenomics era, system-wide overview provided by multi-omics studies contributes valuable insights on algal research in biofuels development (Rai et al, 2016), veterinary medicine (Li et al, 2015), and systemic progression on pathogenesis in liver cancer research (Nie et al, 2016), respectively. Proteomics, as an important technique in multi-omics study, still has limitations, despite improvements that were made in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to determine the potential for canines with diabetes to be used as an alternative animal model of human T1D 10 , and if metabolomic analysis may identify novel biomarkers of the disease. While metabolomic profiles have been studied in healthy dogs 11 , 12 and in several disease states, including inflammatory bowel disease 13 and degenerative valvular disease 14 , information from an untargeted metabolomics assessment of diabetic dogs is lacking. With this study, we evaluated the metabolomic profiles of fasted diabetic versus healthy control dogs, and hypothesized that diabetic dogs have metabolomic perturbations similar to those reported in human T1D patients, including alterations in carbohydrates, branched-chain AA and FA.…”
Section: Introductionmentioning
confidence: 99%